Evaluating to implemantation of free Primary Education (FPE) policy in Mozambique: equity and efficiency approaches (IF-Sophia: revista eletrônica de investigações Filosófica, Científica e Tecnológica, 2015)
In 2003, the government of Mozambique abolished obligatory school fees for grades 1 to 7 with effect from 2004 school year as a means to eradicate the cost barriers of access to school. This intervention became known as Free Primary Education (FPE) Policy. The program was an accomplishment of the initiative launched by the international agencies such as UNICEF and the World Bank in the early 1990s when they emphasised that Universal Primary Education for All (UEA) should become a right and duty. The purpose of the policy implementation was based on theassumption that tuition fees had led to segregation and inequalities in access to school and consequently illiteracy and poverty proliferated in the country. This article evaluates the implementation process of the policy in terms of equity and efficiency addressing three main concerns. Firstly, is the genesis of the policy and associated policies and how previous efforts and agendas faltered to eradicate illiteracy and poverty in Mozambique. Secondly it raises questions concerning policy implementation and the nexus established between equity and efficiency. Therefore,the situation of Malawi and Ghana which followed two unlike implementation methodologies are herein brought in order to show how Mozambique learns from the two countries to generate its own model of policy implementation. Lastly, a logic model is devised which illustrates how the policy was designed, how it operates and which priority efforts to eradicate illiteracy and social disparities in access to school are being prioritised. The results and findings from this study are summed up in the vision that despite some weaknesses in the establishment of (FPE) procedures, the strengths of the policy are leading the country to far reaching outcomes in the sense that access to school is now reaching unreached zones, parents are no longer financially constrained, employment opportunities were created in the education sector and learning needs are slightly being met. The information for this study wascollected mainly through the review of secondary sources such as reports, government documents, academic books and journals on the state of education in Mozambique and other countries in the Sub-Saharan Africa.
Keywords: Array; Array; Array